Análise contrastiva de traduções de curtas-metragens animados de “Pica-Pau” do inglês (americano) para o português (brasileiro) e para o espanhol (mexicano) - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This paper aimed to investigate the translation procedures and their concomitant and disparate applications in translations of Woody Woodpecker animated shorts in the Mexican and Brazilian versions. As part of the research methodology, a review of the literature on Translation Studies took place, focusing on translation procedures, which would be the basis for an analysis of contrastive linguistic nature, encompassing excerpts of fifteen Woody Woodpecker shorts from the 1940s in all the three languages involved (English, Spanish, and Portuguese). Then, the writing of the transcriptions from the original shorts and their versions took place to begin data collection, where these would be subject to analyses per translation procedure. The goal was to identify the simultaneous use or not of a specific translation procedure by both versions when translating a common excerpt from the original. While collecting the data, it was possible to identify the translation procedures of omission, modulation, transposition, amplification, and literal translation as prevalent, whereas the translation procedures of explicitation, borrowing, and calque as less frequent. The analyses showed that there were occurrences of concomitant and disparate applications of a given translation procedure from both versions when translating a related original excerpt. The concomitant applications occurred whenever both versions would share similar grammatical, structural and stylistic aspects, and in some examples, similar cultural features. Meanwhile, the disparate applications occurred due to several factors, among them, grammatical, structural and cultural differences between both versions, particular stylistic choices from the translators, the intended audience for the show, the historical contexts of each country by the time the translations were made, controversial political issues, the censorship of inappropriate contents, among others.
Keywords: Estudos da tradução; Procedimentos técnicos da tradução; Curtas-metragens animados; Pica-Pau; Translation studies; Translation procedures; Animated shorts; Woody Woodpecker; CNPQ::LINGUISTICA, LETRAS E ARTES